2016
DOI: 10.1016/j.joep.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Argument-inconsistency in charity appeals: Statistical information about the scope of the problem decrease helping toward a single identified victim but not helping toward many non-identified victims in a refugee crisis context

Abstract: Argument-inconsistency in charity appeals: Statistical information about the scope of the problem decrease helping toward a single identified victim but not helping toward many nonidentified victims in a refugee crisis context Arvid Erlandsson (corresponding author): Word count: 9596 (excluding abstract and reference list) © 2016. This manuscript version is made available under the Elsevier user license http://www.elsevier.com/open-access/userlicense/1.0/ RUNNING HEAD: HOW STATISTICAL INFORMATION INFLUENCE HEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…For example, an advertisement can try to persuade readers either by appealing to emotions or by appealing to facts and logic (Erlandsson, Västfjäll, Sundfelt, & Slovic, 2016). Advertisements also differ in to what extent they tend to focus on consequences for others or consequences for oneself if complying or not complying (e.g., Fisher, Vandenbosch, & Antia, 2008).…”
Section: Definition Of Negative and Positive Appealsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an advertisement can try to persuade readers either by appealing to emotions or by appealing to facts and logic (Erlandsson, Västfjäll, Sundfelt, & Slovic, 2016). Advertisements also differ in to what extent they tend to focus on consequences for others or consequences for oneself if complying or not complying (e.g., Fisher, Vandenbosch, & Antia, 2008).…”
Section: Definition Of Negative and Positive Appealsmentioning
confidence: 99%
“…Although this approach is common in charitable marketing, there are reasons to question its effectiveness. There are studies that suggest that internal congruence in the charity appeal is important (e.g., Erlandsson et al, 2016). For example, Lee and Aaker (2004) manipulated both type of appeals (gain or loss framed) and type of behavior (prevention or promotion) in a noncharity context.…”
Section: Limitations and Caveatsmentioning
confidence: 99%
“…Further, studies in this area typically compare an identified individual to either a group of identified individuals [ 3 ], to an identified individual and a group [ 26 ], or to statistics [ 22 ]. In addition, work has compared how the inclusion of statistical information influences the impact of help appeals featuring groups and individuals [ 27 ]. Previous studies have not included these various victim presentations in the same between-subjects design.…”
Section: Studymentioning
confidence: 99%
“…On the one hand, several lines of research predict that high numbers of dead or needy people are generally discouraging, and that people will be the most motivated to help when there is a single identified individual in need and when it is possible to help that individual (Bartels, ; Kogut & Ritov, ; Mata, ; Slovic, ; Small, Loewenstein, & Slovic, ; Västfjäll, Slovic, & Mayorga, ; Västfjäll, Slovic, Mayorga, & Peters, ). On the other hand, other lines of research suggest that including statistical information and numbers in charity appeals sometimes can increase prosocial behavior (Bachke, Alfnes, & Wik, ; Cryder, Loewenstein, & Scheines, ; Erlandsson, Västfjäll, Sundfelt, & Slovic, ; Kleber, Dickert, Peters, & Florack, ; Lesner & Rasmussen, ).…”
Section: Introductionmentioning
confidence: 99%